Inappropriate prescribing of drugs for peptic ulcer and gastro-esophageal reflux disease remains a matter of concern: Results from the LAPTOP-PPI cluster randomized trial - Casula, Manuela; Ardoino, Ilaria; Pierini, Laura; Perrella, Lara; Scotti, Stefano; Mucherino, Sara; Orlando, Valentina; Menditto, Enrica; Franchi, Carlotta (Frontiers in Pharmacology, 2025)
BackgroundProton pump inhibitors (PPIs) are among the most commonly and inappropriately prescribed drugs by general practitioners (GPs), resulting in increased risk of adverse outcomes for patients and in avoidable costs for Italy’s National Health Service (NHS). This study aims to assess the effectiveness of a low-cost and easily implementable informative intervention directed at GPs to enhance the appropriate prescription of PPIs.MethodsThe LAPTOP-PPI study is a pragmatic, cluster-randomized controlled trial designed to improve the appropriateness of PPI prescriptions among community-dwelling individuals aged ≥65 years. In June 2021, GPs in the Local Health Units (LHUs) of Bergamo (Northern Italy) and Caserta (Southern Italy) were randomly allocated to either an intervention group (summary reports on prescribing habits, scientific documents on the Italian Medicine Agency’s therapeutic indications, strategies for PPI de-prescribing, along with educational materials for patients), and a control group (standard practice). PPI appropriateness was assessed through an algorithm specifically designed and based on NHS prescription appropriateness and reimbursement criteria. Intervention efficacy was evaluated by comparing data from the baseline period (July 1 to 31 December 2019) with those from the follow-up period (July 1 to 31 December 2021), 6 months after randomization. The analysis was performed on the intention-to-treat principle and according to GP level. To estimate the effectiveness of the intervention, we used a difference-in-differences (DID) approach.ResultsOverall, 942 GPs (540 from Bergamo and 402 from Caserta LHUs) were included in the analysis. At baseline, 171,978 patients aged ≥65 received drug prescriptions for acid-related diseases and were assessable for evaluation of appropriateness. At follow-up, this number was 137,699. The overall inappropriateness rate at baseline among GPs included in the analysis was 57.4% (std.dev. 8.4%) in the intervention arm and 57.6% (std.dev. 8.8%) in the control arm; 6 months after the intervention delivery, they were 59.2% (std.dev. 8.0%) and 58.5% (std.dev. 7.3%), respectively.ConclusionGiven their widespread use, improving the prescription quality of PPIs is a major concern. Educational interventions for GPs and patients are routine strategies to address inappropriateness, but they appear to be insufficient for independently improving prescribing practice, especially in a critical situation such as the post-pandemic period.